The Electric Equipment of Traction Vehicles Current Development and Perspectives - Rastislav Tabacek; Jan Vittek (Communications - Scientific letters of the University of Zilina, 2001)
The electric equipment of traction vehicles has undergone very fast development during the last period. Traction drive was changed dramatically where induction motors took over. Control of induction motors needs sophisticated control circuitry for control of static converters, which produce three-phase current of variable frequency and variable voltage. Performance of the drives and vehicles are then determined by the control techniques, which enable complete automation ofthe train motion, as it is demanded mainly for high-speed service.